A Molecular Level Approach To Elucidate the Supramolecular Packing of Light‐Harvesting Antenna Systems. Issue 56 (13th September 2018) - Thomas, Brijith; Dubey, Rajeev K.; Clabbers, Max T. B.; Gupta, Karthick Babu Sai Sankar; van Genderen, Eric; Jager, Wolter F.; Abrahams, Jan Pieter; Sudholter, Ernst J. R.; de Groot, Huub J. M.
Abstract: The molecular geometry and supramolecular packing of two bichromophoric prototypic light harvesting compoundsD1A2 andD2A2, consisting of two naphthylimide energy donors that were attached to the 1, 7 bay positions of a perylene monoimide diester energy acceptor, have been determined by a hybrid approach using magic angle spinning NMR spectroscopy and electron nano‐crystallography (ENC), followed by modelling. NMR shift constraints, combined with the P 1 ‾ space group obtained from ENC, were used to generate a centrosymmetric dimer of truncated perylene fragments. This racemic packing motif is used in a biased molecular replacement approach to generate a partial 3D electrostatic scattering potential map. Resolving the structure of the bay substituents is guided by the inversion symmetry, and the distance constraints obtained from heteronuclear correlation spectra. The antenna molecules form a pseudocrystalline lattice of antiparallel centrosymmetric dimers with pockets of partially disordered bay substituents. The two molecules in a unit cell form a butterfly‐type arrangement. The hybrid methodology that has been developed is robust and widely applicable for critical structural underpinning of self‐assembling structures of large organic molecules. Abstract : Hybrid theory : The molecular geometry and supramolecular packing of two bichromophoric prototypic light harvesting compoundsD1A2 andD2A2, consisting of two naphthylimide energy donors that were attached to the 1, 7 bay positions of a perylene monoimide diester energy acceptor, have been determined by a hybrid approach using magic angle spinning NMR spectroscopy and electron nano‐crystallography (ENC), followed by modelling